Highly efficient biotransformation of ginsenoside Rb1 and Rg3 using β-galactosidase from Aspergillus sp. Issue 96 (17th October 2015) - Wan, Hui-da; Li, Dan
<x xml:space="preserve">Abstract</x> β-Galactosidase from Aspergillus sp. can transform major ginsenoside Rb1 to rare ginsenoside F2 via ginsenoside Rd. Ginsenoside Rg3 can be selectively hydrolyzed with this β-galactosidase and only ginsenoside Rh2 was obtained as well.